From understanding business guanxi to practising it: a golden rule for MNCs in China. Issue 1 (9th May 2016) - Tam, Steven
Abstract : Purpose: This article reveals a managerial issue that multinational corporations (MNCs) in China are at a strategic crossroad where their employees are competing with the same sources of guanxi networks for different business deals simultaneously. Design/methodology/approach: Triggered by a real company case in China and guided by a literature review on business guanxi, the author bridged them into a specific inquiry, as little was known and should be further examined. Findings: The author identified a paradoxical/applied scenario in MNCs between the use of guanxi and overall firm performance damaged by overusing it. Research limitations/implications: Empirical studies are deemed necessary to seek more understanding between the role of guanxi and MNCs in China. Practical implications: Guanxi is not a straightforward guarantee of business achievements in China. Management should note the influence of its actors – own employees – who can potentially diminish the positive returns of guanxi on overall firm's achievements because of non-obvious interplays among employees and "contacts" on the overlapping guanxi networks. The larger the organisation, the higher the risk is. Originality/value: This article proposes a new line of thoughts for practitioners about the effect of business guanxi on overall firm performance and serves as a starting point for academics to explore empirical research. The concept of overlapping guanxi networks is institutionalised and discussed. A three-step rule is also suggested for MNCs as a basic solution.